Business, core values, and our collective self-deceptions - Mayer, Donald (Henry Stewart Talks, 2023)
Bounded ethicality, Ethical fading, Self-serving bias, Overconfident bias, Homo economicus, Financial crisis, Free market, Environment, Democratic capitalism